Profile of SGPT and SGOT on Male Rats (Rattus norvegicus) Hyperglycemic After Giving Insulin Leaf Extract (Tithonia diversifolia) - Rizki Fitrawan Yuneldi; Tyas Rini Saraswati; Enny Yusuf Wachidah Yuniwarti (Biosaintifika: Journal of Biology & Biology Education, 2018)
The leaves of insulin (Tithonia diversifolia (Hemsl.) A. Gray) are native bush plants from Central America. This plant in Indonesia is often called paitan or kembang bulan. The aim of this research was to know the profile of SGPT and SGOT of male white rat (Rattus norvegicus L.) hyperglycemic after giving insulin leaf extract (Tithonia diversifolia (Hemsl.) A. Gray). This study used 20 male Wistar rats which were divided randomly into 5 groups of treatment. Those were P0 as a group of rats which was not given alloxan and insulin leaf extract, P1 as a group of rats which was given alloxan without insulin leaf extract, P2 as a group of rats which was given alloxan and glibenclamide 2 mg/Body Weight (BW)/day, P3 as a group of rats which was given alloxan and insulin leaf extract 30 mg/BW/day, P4 as a group of rats which was given alloxan and insulin leaf extract 60 mg/BW/day. Each treatment was repeated as many as 4 replications. The results of this study indicated that there was no significant differences in all variables, namely levels of SGPT, SGOT, liver weight, body weight and Hepatosomatic index (HSI), so it can be concluded that giving insulin leaf extract (Tithonia diversifolia (Hemsl.) A. Gray) of 30 mg/BW/day and 60 mg/BW/day could improve liver function of hyperglycemic male white rats (R. norvegicus L.).